2017
DOI: 10.1186/s12885-017-3103-1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of gene expression in relapsed childhood B-acute lymphoblastic leukemia

Abstract: BackgroundRelapsed pediatric B-acute lymphoblastic leukemia (B-ALL) remains as the leading cause of cancer death among children. Other than stem cell transplantation and intensified chemotherapy, no other improved treatment strategies have been approved clinically. Gene expression profiling represents a powerful approach to identify potential biomarkers and new therapeutic targets for various diseases including leukemias. However, inadequate sample size in many individual experiments has failed to provide adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 86 publications
2
25
0
Order By: Relevance
“…We founded that DUXAP10 was up‐regulated both in GSE15471 and GSE16515 datasets, while the expression level of DUXAP10 were found not to be significantly up‐regulation in GSE15932 (fold change >2.0, P < 0.05; Figure A;). To avoid the limitation of small sample sizes in individual study, we then performed meta‐analysis on these three datasets using RankProd approach . Interestingly, DUXAP10 were found to be up‐regulated in meta‐analysis of three microarray datasets (fold change =1.35, P < 0.001; Figure B;).…”
Section: Resultsmentioning
confidence: 99%
“…We founded that DUXAP10 was up‐regulated both in GSE15471 and GSE16515 datasets, while the expression level of DUXAP10 were found not to be significantly up‐regulation in GSE15932 (fold change >2.0, P < 0.05; Figure A;). To avoid the limitation of small sample sizes in individual study, we then performed meta‐analysis on these three datasets using RankProd approach . Interestingly, DUXAP10 were found to be up‐regulated in meta‐analysis of three microarray datasets (fold change =1.35, P < 0.001; Figure B;).…”
Section: Resultsmentioning
confidence: 99%
“…Analyzed individually, these studies identified dozens of genes misexpressed on relapse (13)(14)(15). A recent metaanalysis of these three studies (40) identified hundreds more, but some misexpressed genes (e. g., AURKB) were not identified, and others had surprisingly lowconfidence values (e.g., false discovery rate = 0). We, therefore, Fig.…”
Section: Transcriptome Analysis Of Paired Diagnostic/relapsed B-all Smentioning
confidence: 99%
“…Despite the great promise of microarray technology for understanding β‐hemoglobinopathies (Bianchi et al., ; Flanagan et al., ), individual studies have various limitations, including the production of results that are not reproducible or conflicting (Melboucy‐Belkhir et al., ). These issues are likely a result of differences in experimental platforms, samples, standardization methods, and analytical methods, causing discrepancies in the microarray data obtained from different laboratories (Chow, Alias, & Jamal, ). Hence, much valuable information may be missed.…”
Section: Discussionmentioning
confidence: 99%